INVESTIGATING THE EFFECT OF ORGANIZATIONAL CLIMATE ON TOURISM SERVICE QUALITY AT IRAQI FIRST-CLASS HOTELS - Adel Turki Al-khalidy; Abdulmohsin Jawad Keshwan; Zaid Abdulzahra Jaffar (Scholar Express Journal, 2023)
The aim of this study is to investigate the effect of organizational climate on service quality of first class hotels in the Iraqi context. In this study, the method was quantitative, and the population was the employees of hotels (300 Employees) while the sample of the study was 270 employees. Data was collected by using questionnaire which consisted (27) statements. According to the findings of the study, there is a direct positive influence between organizational climate and tourism service quality.
Keywords: Organizational Climate; Tourism Service Quality; Effect